The Ramadan cookbook : 80 delicious recipes perfect for Ramadan, Eid, and celebrating throughout the year - Karolia, Anisa (Countryman Press, 2024)
Quick, easy, flavorful, and filling--these recipes will become the go-to for suhoor, iftar, and other special, festive meals. In this cookbook, readers will find all the recipes they need to make Ramadan meals family-friendly and fuss-free. For Anisa Karolia--who is known for sharing her family's traditional Indian and Malawi recipes--Ramadan, the month of fasting to celebrate the ninth month of the Islamic calendar, is about self-reflection, becoming closer to her religion, and sharing the holiday with loved ones. Of course, at suhoor and iftar, the pre-dawn and fast-breaking meals of Ramadan respectively, this sharing means dining together. From comforting classics like masala roast chicken to fusion favorites like cauliflower Manchurian, the recipes in "The Ramadan cookbook" make it possible for readers to share simple, delicious recipes with family and friends. Beautifully photographed and featuring recipes for sides, chutneys, flatbreads, refreshments, and sweets, this book ensures that readers will eat well before and after fasting, as well as throughout the year.